Blocking Stroke-Induced Immunodeficiency Increases CNS Antigen-Specific Autoreactivity But Does Not Worsen Functional Outcome after Experimental Stroke - Römer, Christine (J Neurosci, 2015)
Stroke-induced immunodepression (SIDS) is an essential cause of poststroke infections. Pharmacological inhibition of SIDS appears promising in preventing life-threatening infections in stroke patients. However, SIDS might represent an adaptive mechanism preventing autoreactive immune responses after stroke. To address this, we used myelin oligodendrocyte glycoprotein (MOG) T-cell receptor transgenic (2D2) mice where >80% of peripheral CD4(+) T cells express a functional receptor for MOG. We investigated in a murine model of middle cerebral artery occlusion the effect of blocking SIDS by inhibiting body's main stress axes, the sympathetic nervous system (SNS) with propranolol and the hypothalamic-pituitary-adrenal axis (HPA) with mifepristone. Blockade of both stress axes robustly reduced infarct volumes, decreased infection rate, and increased long-term survival of 2D2 and C57BL/6J wild-type mice. Despite these protective effects, blockade of SIDS increased CNS antigen-specific Type1 T helper cell (Th1) responses in the brains of 2D2 mice 14 d after middle cerebral artery occlusion. One month after experimental stroke, 2D2 mice developed signs of polyradiculitis, which were diminished by SIDS blockade. Adoptive transfer of CD4(+) T cells, isolated from 2D2 mice, into lymphocyte-deficient Rag-1KO mice did not reveal differences between SIDS blockade and vehicle treatment in functional long-term outcome after stroke. In conclusion, inhibiting SIDS by pharmacological blockade of body's stress axes increases autoreactive CNS antigen-specific T-cell responses in the brain but does not worsen functional long-term outcome after experimental stroke, even in a mouse model where CNS antigen-specific autoreactive T-cell responses are boosted.